2012
DOI: 10.1021/ie3021686
|View full text |Cite
|
Sign up to set email alerts
|

Autothermal Partial Oxidation of Glycerol to Syngas over Pt-, LaMnO3-, and Pt/LaMnO3-Coated Monoliths

Abstract: Glycerol and glycerol/water solution were converted to syngas over Pt-, LaMnO 3 -, and Pt/LaMnO 3 -coated monoliths under autothermal partial oxidation. XRD and SEM were used to characterize the phase compositions and surface morphologies of freshly prepared and postreaction catalysts. A continuous fixed-bed design, without an upstream vaporizer or external heat supply, was operated at millisecond contact times. Among the catalysts used in this study, Pt was the least reactive, and its activity was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…At 800 C decreasing the oxygen content in the feed to 10% increases exit H 2 content by~3% and decreases CO 2 content by~5%, while CO concentration remains constant. Syngas selectivity (SH 2~6 0% and SCO~60%) is close to that obtained at millisecond contact times for cordieritesupported LaMnO 3 and LaNiO 3 [8,28], while in steam reforming of glycerol SCO 2 is higher than SCO [27].…”
Section: Glycerol Reformingsupporting
confidence: 75%
See 2 more Smart Citations
“…At 800 C decreasing the oxygen content in the feed to 10% increases exit H 2 content by~3% and decreases CO 2 content by~5%, while CO concentration remains constant. Syngas selectivity (SH 2~6 0% and SCO~60%) is close to that obtained at millisecond contact times for cordieritesupported LaMnO 3 and LaNiO 3 [8,28], while in steam reforming of glycerol SCO 2 is higher than SCO [27].…”
Section: Glycerol Reformingsupporting
confidence: 75%
“…Concentrations of such byproducts as CH 4 and C 2 H 4 are reasonably low, though apparently liquid phase by-products (acetone, acetaldehyde, acrolein, methanol, ethanol, hydroxyacetone, acetic acid, propionic acid, propylene glycol, ethylene glycol, acrolein etc.) [8,27,28] are formed in this reaction in the low-temperature range.…”
Section: Glycerol Reformingmentioning
confidence: 95%
See 1 more Smart Citation
“…The higher interaction between the deposited Pt metal and the perovskite support almost completely inhibited sintering phenomena without altering the catalyst's POX activity. SEM pictures showed that Pt grain size distribution was not changed over 28‐h TOS, as shown in Figure . The data were not similar for Ni and Pd.…”
Section: Generic Catalytic Technologiesmentioning
confidence: 88%
“…The main drawback of Rh/CeO 2 ‐based catalyst was the sintering phenomena observed over TOS. Liu and Lin observed that this drawback can be remedied with LaMnO 3 perovskite as a Pt‐based POX catalyst. The higher interaction between the deposited Pt metal and the perovskite support almost completely inhibited sintering phenomena without altering the catalyst's POX activity.…”
Section: Generic Catalytic Technologiesmentioning
confidence: 99%